Characterizing and predicting sublethal shifts in mobility by multiple stored product insects over time to an old and novel contact insecticide in three key stored commodities. Issue 4 (20th January 2021) - Morrison, William R; Arthur, Frank H; Bruce, Alexander
Abstract: BACKGROUND: There has been a push to diversify integrated pest management (IPM) programs away from exclusive fumigant use in food facilities. Residual insecticides increasingly have been included among plans. In stored products, sublethal toxicity has been neglected in favor of evaluating direct mortality. Here, we evaluated the movement of Tribolium castaneum, Rhyzopertha dominica, Sitophilus oryzae and Sitophilus zeamais in response to aged residues of an existing (Diacon IGR+® with 11.4% methoprene + 4.75% deltamethrin) and novel (Gravista® with 2.85% methoprene + 1.2% deltamethrin + 33.3% piperonyl butoxide synergist) residual insecticide. RESULTS: Using the maximum labeled rate and two exposure times for each species, we assessed distance moved and velocity on wheat, rice and corn. Assessments were made from commodity residues aged between 0 and 12 months (at 3‐month intervals). We found that after exposure, movement was reduced by 50–88% and equally by adults exposed to each insecticide formulation compared to untreated controls. After initial application, predicted distance moved increased from 4 to 14 m then 28 m in a 24 h period at 3 and 12 months post‐application, respectively. Effectiveness of each insecticide at suppressing movement generally declined by 9–12 month post‐application. CONCLUSIONS: Given the quick and dramatic increases in sublethal movement after initial application, our results suggest that sanitation programs in post‐harvest environments are extremely important and it may be beneficial to pair chemical control with monitoring to prevent dispersal of affected insects to new areas of a facility. Published 2020. This article is a U.S. Government work and is in the public domain in the USA Abstract : In this study, we evaluated the movement of Tribolium castaneum, Rhyzopertha dominica, Sitophilus oryzae and Sitophilus zeamais in response to aged residues of an existing (Diacon IGR+ with 11.4% methoprene +4.75% deltamethrin) and novel (Gravista® with 2.85% methoprene +1.2% deltamethrin +33.3% piperonyl butoxide synergist) residual insecticide, and found that after exposure, movement was reduced by 50–88% and equally by each formulation compared to untreated controls. After initial application, predicted distance moved increased from 4 m to 14 m then 28 m in a 24 h period at 3 and 12 months post‐application, respectively. Published 2020. This article is a U.S. Government work and is in the public domain in the USA